FAMILY FEATURES AND ACADEMIC AND SOCIAL-EMOTIONAL DEVELOPMENT OF LEFT-BEHIND CHILDREN IN HUBEI, CHINA - Yunlei Hu (MOJES: Malaysian Online Journal of Educational Sciences, 2024)
Nearly half of children in China were affected by migration, and more than one-third of rural children had been left at home, classified as rural left-behind children (LBC). Despite numerous studies on migration and LBC, little research has investigated the issues of LBC by connecting their development with family features. This study aimed to identify associations between family features and children’s academic performance and social-emotional development, focusing on differences between LBC and non-LBC. A quantitative method was applied, covering 548 primary school children in Shennongjia District, Hubei Province, China. Disparities between LBC and non-LBC were found in their social and emotional development, which disappeared among one-child families. Surprisingly, no significant differences were found in their academic performance, behavioral development, or certain demographic features, including gender, age, and family economic status. Furthermore, family features associated with children’s development were found to be family structure, maternal factors such as maternal migration status and mothers’ education, fathers’ migration status, and the role of caregivers. Indeed, maternal migration status was identified as a vitally influential predictor of children’s social-emotional development, while fathers’ migration status was another influential predictor of children’s emotional development. Drawing from ecological systems theory, this study underscored the importance of family in children’s development and highlighted the compensatory function of schools and governments for disadvantaged contexts such as migration through educational policies and practices. Concurrently, it emphasized the imperative for heightened attention to the social and emotional well-being of LBC and comprehensive intervention support for stakeholders.